Political Economy of Cooperative Federalism in Germany. Issues and Implementation - Sturm, Roland (Cooperative Federalism in South Asia and Europe. Contemporary Issues and Trends, 2023)
In the literature, cooperative federalism is mostly discussed as a political project that concentrates on steering intergovernmental relations. This approach tends to forget that political cooperation is based on the opportunities provided by regional economic diversity. A closer look at the political economy of cooperative federalism helps us understand the restrictions under which cooperative federalism has to make decisions these days. The political economy of federalism manifests itself in patterns of economic geography. It creates regions that often follow more of a functional than a constitutional logic. In contrast to federalism's legal efforts to accommodate social conflict by decentralization and power-sharing, economic decentralization is only sometimes supportive of constitutional federalism. Economic regions are not of comparable importance. This creates regional imbalances that challenge at least the traditional view of federations as contracts between equals. This then leads us to the question of the relationship between economic challenges and their territorial consequences. As a next step, we discuss the rationale of economic regionalism, its economic justifications and economic logic. Section 4 deals with the consequences of globalization for regional economic differences and regional policy responses. The last section looks at the constitutional rule for co-operative federalism in Germany.
CRIS-Team Scopus Importer:2024-12-16